2012
DOI: 10.1088/1742-5468/2012/07/p07021
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement ofTcin the superconductor–insulator phase transition on scale-free networks

Abstract: A road map to understand the relation between the onset of the superconducting state with the particular optimum heterogeneity in granular superconductors is to study a Random Tranverse Ising Model on complex networks with a scale-free degree distribution regularized by and exponential cutoff p(k) ∝ k −γ exp [−k/ξ]. In this paper we characterize in detail the phase diagram of this model and its critical indices both on annealed and quenched networks. To uncover the phase diagram of the model we use the tools o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 36 publications
6
34
0
Order By: Relevance
“…This result points again toward the importance of connectivity and an optimum inhomogeneity for high critical temperature (12,26). It is also in qualitative agreement with the theoretical prediction of the increase of T c in a granular superconductor on an annealed complex network with a finite cutoff (55,56). In fact, for a power-law distribution of links in a granular superconductor with an exponent α ¼ 2.6 the critical temperature is predicted to increase as a function of the cutoff with an exponent 3 − α, as observed experimentally.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This result points again toward the importance of connectivity and an optimum inhomogeneity for high critical temperature (12,26). It is also in qualitative agreement with the theoretical prediction of the increase of T c in a granular superconductor on an annealed complex network with a finite cutoff (55,56). In fact, for a power-law distribution of links in a granular superconductor with an exponent α ¼ 2.6 the critical temperature is predicted to increase as a function of the cutoff with an exponent 3 − α, as observed experimentally.…”
Section: Resultssupporting
confidence: 86%
“…Our quantitative results should be tested against theories of composite, granular superconductors proposed for cuprates (10,14,15,25,(30)(31)(32)(55)(56)(57)(58)(59)(60)(61)(62). The X-ray data indicate that these theories must take into account not only the usual superconducting proximity effects, but also the effects of the strains the two components exert on each other.…”
Section: Discussionmentioning
confidence: 91%
“…[43][44][45][46] The formation of nanoscale ordered grains in YBa 2 Cu 3 O 6+y with Ortho-II lattice in the basal plane is highly relevant for the electronic structure of the system and for models of superconductor-to-insulator transition. 19,20 The oxygen chain puddles had the Ortho-II lattice superstructure, like the YBa 2 Cu 3 O 6.5 , which showed band folding and Fermi surface reconstruction measured by photoemission and quantum oscillations experiments. 48,49 The granular structure of Ortho-II puddles favored the 7 K superconductivity; in fact, in the rapidly quenched sample from T > 450 K, where the Ortho-II puddles were not formed, the critical temperature drops to zero.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Recently, several theories have been proposed based on the presence in HTS of networks of nanoscale superconducting grains. [16][17][18][19][20][21] The nanoscale phase separation related to the selforganization of defects is not a unique feature of cuprates like superoxygenated La 2 CuO 4+y , 22 La 2−x Sr x CuO 4 , 6,23,24 and Bi 2 Sr 2 CaCu 2 O 8+y , 25 but it has been found also in Al 1−x Mg x B 2 , 26 doped iron-chalcogenides, [27][28][29] and other functional materials like manganites. 30 Thermal treatments control defect organization 31-34 on photo-induced effects, 35 muon-spin resonance (μSR) 36 showed that lattice complexity controls T c in YBa 2 Cu 3 O 6+y .…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Griffiths phases have been reported in a study of the random transverse Ising model on complex networks with a scale-free degree distribution regularized by and exponential cutoff p(k) ∝ k −γ exp[−k/ξ ] [42]. This model was devised to understand the relation between the onset of the superconducting state with the particular optimum heterogeneity in granular superconductors.…”
Section: Discussionmentioning
confidence: 99%